Die Restitution des Ullstein-Verlags (1945-52). Remigration, Ränke, Rückgabe: Der steinige Weg einer Berliner Traditionsfirma - Berndt, Juliane (Europäisch-jüdische Studien - Beiträge, 2020)
After the end of the Second World War, the Ullstein family fought to reclaim the publishing house that they were forced to sell in 1934. But the Americans needed the company's printing plant in the Tempelhof district of Berlin for their reeducation program, and as a result delayed its restitution. At the same time, the Berlin senate feared reviving the Ullsteins' legendary publishing house would spark a newspaper war in West Berlin.